2008
DOI: 10.1097/ijg.0b013e31814b97fd
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Among Humphrey Field Analyzer, Microperimetry, and Heidelberg Retina Tomograph in the Evaluation of Macula in Primary Open Angle Glaucoma

Abstract: Perimetric macular changes can occur while macular topographic remains stable in patients with glaucoma. MP-1 correlates with HFA in detecting glaucomatous visual field defect in macular area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 11 publications
1
31
1
2
Order By: Relevance
“…Regarding the good correlation between SLO-MP and SAP, our findings are consistent with the few previous studies comparing these two modalities 13 14 15. In a study evaluating primary open-angle glaucoma patients with localised RNFL defects, Orzalesi et al 13 found a good correlation between microperimetry with SLO using a 40° field of view and SAP of the central 30°.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding the good correlation between SLO-MP and SAP, our findings are consistent with the few previous studies comparing these two modalities 13 14 15. In a study evaluating primary open-angle glaucoma patients with localised RNFL defects, Orzalesi et al 13 found a good correlation between microperimetry with SLO using a 40° field of view and SAP of the central 30°.…”
Section: Discussionsupporting
confidence: 91%
“…In a study evaluating primary open-angle glaucoma patients with localised RNFL defects, Orzalesi et al 13 found a good correlation between microperimetry with SLO using a 40° field of view and SAP of the central 30°. A more recent study using a different device, liquid crystal display microperimetry, demonstrated that microperimetry correlated with SAP in detecting glaucomatous VF defects in the macular area of patients with primary-open angle glaucoma 14. Finally, microperimetry in eyes with advanced glaucomatous damage (central island of vision) correlated with Goldmann perimetry results and could be useful in detecting retinal sensitivity in the remaining areas of RNFL 15…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lima et al [8] demonstrated that macular sensitivity evaluated by SLO microperimetry had a significant correlation with SAP paracentral visual field defects. Ozturk et al [28] reported MP-1 correlated with HFA in detecting glaucomatous visual field defects in the macular area. These reports are in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The MAIA microperimeter is a relatively new instrument equipped with a scanning laser ophthalmoscope with an eye tracking system. [23] MAIA has been used to determine the central retinal sensitivities of eyes with glaucoma,[24] age-related macular degeneration (AMD). [25] macular hole,[26] and other ophthalmic diseases.…”
Section: Methodsmentioning
confidence: 99%